2002
DOI: 10.1186/cc1528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemofiltration filter adsorption on circulating IL-6 levels in septic rats

Abstract: IntroductionNumerous studies have shown that hemofiltration using porous synthetic membranes can and does remove a wide range of substances that mediate inflammation from the plasma [1][2]. Limited evidence supports the notion that this treatment can also influence circulating plasma concentrations of various mediators [3][4][5] and mounting evidence suggests that these manipulations have important biologic effects [6][7][8]. Despite these advances, there are no randomized clinical trials demonstrating that he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A period of time was given as a range of 0–2, 2–4, 4–6, 6–10, and 10–infinity hours in this figure (expressed as gray color gradation). Marks numbering from 1 to 8 displayed referenced reports on IL-6 removal; 1 and 2 are referring to two differing settings of our study ( 1 is for standard volume hemofiltration and 2 is for high-volume hemofiltration); 3 , Laurent et al [ 19 ] and 4 , Nagashima et al [ 20 ], studies on whole-body ischemia/reperfusion injury; 5 , Kellum et al [ 34 ], 6 , Bellomo et al [ 21 ], 7 , Lu et al [ 35 ], and 8 , Rogiers et al [ 33 ], studies on a sepsis animal model. The studies, 1 , 2 , and 5 – 8 , used the same filter of AN69; therefore, SC was set at 0.3 according to our pilot data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A period of time was given as a range of 0–2, 2–4, 4–6, 6–10, and 10–infinity hours in this figure (expressed as gray color gradation). Marks numbering from 1 to 8 displayed referenced reports on IL-6 removal; 1 and 2 are referring to two differing settings of our study ( 1 is for standard volume hemofiltration and 2 is for high-volume hemofiltration); 3 , Laurent et al [ 19 ] and 4 , Nagashima et al [ 20 ], studies on whole-body ischemia/reperfusion injury; 5 , Kellum et al [ 34 ], 6 , Bellomo et al [ 21 ], 7 , Lu et al [ 35 ], and 8 , Rogiers et al [ 33 ], studies on a sepsis animal model. The studies, 1 , 2 , and 5 – 8 , used the same filter of AN69; therefore, SC was set at 0.3 according to our pilot data.…”
Section: Discussionmentioning
confidence: 99%
“…Kellum et al [ 34 ] reported blood IL-6 levels during the hemofiltration in sepsis. They showed significantly lower blood IL-6 levels (17 pg/mL) in hemofiltration-treated animals than non-treated animals (62 pg/mL) using the cecal ligation and puncture model of rats.…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment to compare the relative effects of sieving and adsorption on plasma IL-6 following CLP in rats [20], we found that hemoadsorption was the main mechanism of removal. Hemoadsorption is dependent on membrane material and, during hemofiltration, on filtration operating parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Protein adsorption to all types of artificial membranes is well described, occurring in the first 20 min of blood-membrane interface [14,15,16]. This mode of clearance has previously been documented for other proteins, such as cytokines, in both laboratory and human studies of CVVH in sepsis [17,18,19,20,21]. Although protein adsorption occurs with AN69 and PS membranes, PMMA membranes were designed specifically for protein adsorption to limit β 2 -microglobulin accumulation and to prevent dialysis-related amyloidosis [22].…”
Section: Introductionmentioning
confidence: 90%